Molecular epidemiology of methicillin‐resistant Staphylococcus aureus in Switzerland: sampling only invasive isolates does not allow a representative description of the local diversity of clones1. (4th March 2013) - Senn, L.; Basset, P.; Greub, G.; Prod'hom, G.; Frei, R.; Zbinden, R.; Gaia, V.; Balmelli, C.; Pfyffer, G. E.; Mühlemann, K.; Zanetti, G.; Blanc, D. S.; et al.
Abstract We conducted a molecular study of MRSA isolated in Swiss hospitals, including the first five consecutive isolates recovered from blood cultures and the first ten isolates recovered from other sites in newly identified carriers. Among 73 MRSA isolates, 44 different double locus sequence typing (DLST) types and 32 spa types were observed. Most isolates belonged to the NewYork/Japan, the UK‐EMRSA‐15, the South German and the Berlin clones. In a country with a low to moderate MRSA incidence, inclusion of non‐invasive isolates allowed a more accurate description of the diversity.